2022
DOI: 10.1002/emp2.12865
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on the associated complications of high‐risk conditions in a statewide pediatric emergency network

Abstract: Background The COVID‐19 pandemic affected the volume and epidemiology of pediatric emergency department (ED) visits. We aimed to determine the rate of associated complications for 16 high‐risk conditions in a Michigan statewide network of academic and community EDs during the pandemic. Methods We conducted a cross‐sectional study of pediatric ED visits among a network of 5 Michigan health systems during the pre‐pandemic (March 1, 2019–March 10, 2020) and pandemic (March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The COVID pandemic further underscored the ongoing need for nimble, multi‐centered, multi‐disciplinary, collaborative approaches to understand the rapidly evolving epidemiology of the virus, and assess the impact, efficacy, and effectiveness of various operational and therapeutic interventions. Our recent work on COVID's impact on diagnostic delays across 14 EDs in Michigan 3 and a survey on the impact of COVID on provider burnout and innovation across 74 EDs in 28 countries 4 has revealed that EDs are willing to commit site resources to contribute data for research in emergency care. To overcome the shortcomings of centralized data approaches, a distributed/de‐centralized approach called federated data health networks (FDHN) has been successfully deployed in COVID research; this has opened the potential for similar approaches to emergency care network‐based research 5,6 …”
Section: Moving Toward a De‐centralized Approachmentioning
confidence: 99%
“…The COVID pandemic further underscored the ongoing need for nimble, multi‐centered, multi‐disciplinary, collaborative approaches to understand the rapidly evolving epidemiology of the virus, and assess the impact, efficacy, and effectiveness of various operational and therapeutic interventions. Our recent work on COVID's impact on diagnostic delays across 14 EDs in Michigan 3 and a survey on the impact of COVID on provider burnout and innovation across 74 EDs in 28 countries 4 has revealed that EDs are willing to commit site resources to contribute data for research in emergency care. To overcome the shortcomings of centralized data approaches, a distributed/de‐centralized approach called federated data health networks (FDHN) has been successfully deployed in COVID research; this has opened the potential for similar approaches to emergency care network‐based research 5,6 …”
Section: Moving Toward a De‐centralized Approachmentioning
confidence: 99%